E-Selectin and restenosis after femoropopliteal angioplasty: prognostic impact of the Ser128Arg genotype and plasma levels - Mlekusch, Wolfgang; Exner, Markus; Schillinger, Martin; Sabeti, Schila; Mannhalter, Christine; Minar, Erich; Wagner, Oswald (Thrombosis and Haemostasis, 2004)
Perivascular inflammation plays a key role in the development of restenosis after percutaneous transluminal angioplasty (PTA).The adherence of leucocytes to the activated endothelium, an essential feature in the restenotic process, is mediated by the cellular adhesion molecule E-Selectin. A DNA polymorphism in the regulator region of E-Selectin at codon 561 (Ser128Arg) is suggested to modulate the molecule’s physiological effects. Therefore, we investigated the association between the E-Selectin Ser128Arg genotype, E-Selectin plasma levels and restenosis after femoropopliteal PTA. We prospectively studied 175 consecutive patients with peripheral artery disease and intermittent claudication (n=126) or critical limb ischemia (n=49) who underwent primary successful femoropopliteal balloon angioplasty. E-Selectin Ser128Arg genotype and baseline E-Selectin plasma levels were determined and patients were followed up for median 12 months (IQR 11 to 14, total range 6 to 24) for the occurrence of postangioplasty restenosis (≥50%). E-Selectin plasma levels in homozygous Arg128Arg and heterozygous Ser128Arg patients were significantly higher compared to wildtype Ser128Ser patients (p=0.041). Patency rates for wildtype Ser128Ser, heterozygous Ser128Arg and homozygous Ser128Ser patients were 57%, 44% and 50% at 6 months, and 46%, 40% and 17%, at 12 months, respectively (Log Rank p=0.31). Patency rates for increasing tertiles of E-Selectin were 61%, 58% and 37% at 6 months, and 54%, 45% and 30% at 12 months, respectively (Log Rank p=0.020). Patients with an E-Selectin plasma level above 44.9 mg/dL (third tertile) had an 1.9-fold increased adjusted risk for restenosis (95% CI 1.09 to 3.30). E-Selectin plasma levels are modulated by the E-Selectin Ser128Arg genotype, and predict the risk for restenosis after PTA in patients with PAD. A direct association of the Ser128Arg polymorphism with late postangioplasty failure could not be demonstrated.
Keywords: Angioplasty; restenosis; genes; polymorphism; E-Selectin